The Beauty of the City - Körmendy, Imre (4D Journal of Landscape Architecture and Garden Art, 2013)
The article highlights that the concept of urban beauty requires a multifaceted approach, as different people find it in various elements. For some, geometric order defines beauty, while for others, irregularities or the historical and artistic values of buildings enhance the city’s aesthetic appeal. The study emphasizes the marks of time, the wear on old buildings, and modern urban phenomena. Urban beauty is thus a complex and evolving phenomenon, manifesting in the interaction between architectural elements of the past and the present.